Surgical Outcome of Isolated Extradural Hematomas Operated in a Teaching Hospital in Western Nepal - Karmacharya, Balgopal; Yogi, Nikunja; Pun, Benju (Nepal Journal of Neuroscience, 2019)
The aim of this determine the causes, frequency, location of isolated extradural hematomas in patients presenting with head injury and to find out the outcome of surgery in such patients. This is prospective observational study was conducted in the Neurosurgery Unit of Manipal Teaching Hospital from January 2012 to January 2017. All patients who presented with headinjury and had isolated extradural hematomas were included in the study. Total number of patients admitted with diagnosis of extradural hematomas during that time period was 169 among which 94 patients underwent surgical treatment. Descriptive statistics data including age, gender, causes of injury, severity of head injury and Glasgow outcome scale were studied. Results in proportion and percentages were calculated by using Microsoft Excel 2013.There were 169 patients who had isolated extradural hematomas. Among them, 75 patients were managed conservatively and 94 underwent craniotomy for evacuation of hematoma. This group of 94 patients who operative treatment was taken for this study. Male: female ratio was 1.6:1. Mean age was 23 years. Most of patients were in 20-40 age groups. Causes of extradural hematomas included motor vehicle accidents, falls and assaults. Mild and moderate head injury was present in 53 (56.38%) and 32 (34.0%) patients. Seventy nine patients (84.05%) of patients had good recovery while 3 (3.19%) patients expired.